1985
DOI: 10.1093/sleep/8.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic Alternating Pattern as a Physiologic Component of Normal NREM Sleep

Abstract: Summary: The cyclic alternating pattern (CAP) is a long-lasting periodic activity consisting of two alternate electroencephalogram (EEG) patterns. This variation in EEG is closely related to fluctuations in the level of arousal that characterize two different functional states in the arousal control mechanism. We studied 20 sleep records of 10 healthy subjects to see if CAP appears under physiologic conditions. During NREM sleep, CAP corresponded to a periodic succession of spontaneous phasic phenomena recurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
180
1
9

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(196 citation statements)
references
References 9 publications
6
180
1
9
Order By: Relevance
“…Cyclic alternating pattern (CAP) is an EEG-derived measure of sleep instability, which is reflected as periodic EEG activity during NREM sleep. 68,69 In contrast, periods of Non-CAP are indicative of consolidated sleep. CAP is somewhat distinct from typically measured arousals from sleep, both as a phenomenon and in terms of how they are scored.…”
Section: Microstructure Measures Of Sleep In Cfs/mementioning
confidence: 99%
“…Cyclic alternating pattern (CAP) is an EEG-derived measure of sleep instability, which is reflected as periodic EEG activity during NREM sleep. 68,69 In contrast, periods of Non-CAP are indicative of consolidated sleep. CAP is somewhat distinct from typically measured arousals from sleep, both as a phenomenon and in terms of how they are scored.…”
Section: Microstructure Measures Of Sleep In Cfs/mementioning
confidence: 99%
“…In addition to these relatively fast EEG oscillations, some studies have demonstrated infraslow fluctuations in, for instance, neuronal population activity (2-5), EEG power (5-9), discrete sleep events (arousals, spindles, K complexes) (9)(10)(11)(12), as well as in the occurrence of epileptic events (4,11,13). These observations have raised the possibility that the human cortex may generate infraslow oscillations (ISOs) underlying such fluctuations.…”
mentioning
confidence: 99%
“…[5][6][7] Studies investigating sleep structure have led to the identification of a natural electroencephalographic arousal rhythm within the non-REM sleep stages, related to transient lightenings of sleep depth, known as the cyclic alternating pattern (CAP). 8,9 CAP corresponds to a prolonged oscillation of the arousal level, whereas the complementary condition, non-CAP (NCAP), is closely related to a degree of stability in sleep depth. 8,9 Functionally, CAP translates a condition of sustained arousal instability; however, the arousal swings that characterize CAP sequences are not driven by any motor or respiratory disturbances and are associated with variations of autonomic activity.…”
mentioning
confidence: 99%
“…8,9 Functionally, CAP translates a condition of sustained arousal instability; however, the arousal swings that characterize CAP sequences are not driven by any motor or respiratory disturbances and are associated with variations of autonomic activity. 8,9 Spectral analysis studies reported an increase in the low-frequency (LF) and a decrease in the high-frequency (HF) component of heart rate variability (HRV) during CAP compared with non-CAP sequences, 10,11 suggesting the occurrence of nighttime periods of relative sympathetic activation even during phases, like non-REM sleep, characterized by an increase in the background level of parasympathetic activity. These findings would indicate that surges of sympathetic activity may occur not only during REM.…”
mentioning
confidence: 99%